Factors Affecting Online Health Promotion Program Adherence Among People with Disabilities - Madison Mintz; Robert A. Oster; Jereme Wilroy; James H. Rimmer (Disabilities)
As online health and wellness programs become more ubiquitous post-pandemic, there is a need to better understand how people with physical disabilities respond to different types of program offerings. Online health promotion programs have become popular in the disability community, and programs offer a range of activities across various wellness domains (e.g., exercise, nutrition). This study examined factors predicting adherence to three different types of online health promotion programs tailored for people with physical disabilities. A survey was developed to examine factors associated with high, moderate, and low adherence to three different types of health promotion programs. Participants who completed an online wellness program were sent a survey that asked questions related to adherence to a range of wellness activities. The three programs included the MENTOR (Mindfulness, Exercise, and Nutrition to Optimize Resilience), GROWTH (Growing Resilience Out of Wellness and Thoughtful Habits), and SOSE (State of Slim Everybody) programs, all of which focus on different self-care strategies. MENTOR focused on educating participants about mindfulness, exercise, and nutrition; GROWTH aimed to deliver mental and emotional health techniques, while SOSE’s purpose was to teach participants how to implement healthy weight loss, weight management, and daily exercise practices. Results indicated that participant perceptions of program delivery, specifically programs being disability friendly, virtual environment enjoyment, having positive instructor relationships, adaptable content, the instructor’s knowledge about disability, the instructor’s use of appropriate language, and program satisfaction, affected the likelihood of high adherence among people with physical disabilities enrolled in the health and wellness programs.